Pengaruh Nilai Tukar, PDB, Inflasi dan Harga Emas di Korea Stock Exchange - Birrul Walidain; Idah Zuhroh (Program Studi Ekonomi Pembangunan, 2020)
Stock Price Index is a reflection of the economic conditions of a country when the stock price index shows an increase means that the economy is conducive and vice versa. This study aims to analyze the development of macroeconomic factors on the stock price index on the Korea Stock Exchange. The data used in this study are secondary in the form of data from quarter I-IV during the period 2014 - 2018. Data analysis techniques using multiple linear regression analysis with the help of statistical software program Eviews9. The results of the study show that Exchange Rates, Gross Domestic Product (GDP), Inflation, and World Gold Prices simultaneously influence the Stock Price Index on the Korea Stock Exchange with a calculated F-value (0.002159) < 0.05. T-test results show that Exchange Rates have a significant negative effect. GDP has a significant positive effect on the stock price index on the Korea Stock Exchange, then inflation and world gold prices do not have an influence on the stock price index on the Korea Stock Exchange.